Monte Carlo study of the evolution of diffuse scattering and coherent modulation during h.c.p. to f.c.c. martensitic transition - II. Domain growth kinetics by spinodal process - Shrestha S.P.; Pandey D. (My University, 2025)
Monte Carlo techniques are employed to study the kinetics of h.c.p. (2H) to f.c.c. (3C) martensitic transition by spin flip dynamics using a 1-D (one-dimensional) Ising model. The characteristic length scale is shown to exhibit t0.5 dependence as confirmed by direct domain counting as well as dynamical scaling of the pair correlation functions. The diffuse scattering at late stages can be predicted using a scaling function for the pair correlations. The predicted evolution of the diffuse scattering pattern for the spinodal regime is in qualitative agreement with the experimentally observed patterns for ZnS single crystals. Copyright © 1996 Acta Metallurgica Inc.